Enabling mental health student nurses to work co-productively. Issue 6 (11th October 2019) - Best, Stephanie; Koski, Arja; Walsh, Lynne; Vuokila-Oikkonen, Päivi
Abstract : Purpose: The purpose of this paper is to investigate the use of innovative teaching methods and share a four-step model, to promote the use of co-production in mental health practice. Design/methodology/approach: The case study approach highlights three real-life examples of day to day experiences in mental health nurse education with innovative approaches to sharing and developing co-production skills and attitudes in mental health student nurses. Findings: The case studies highlight three settings where undergraduate mental health nurses experience co-production through a world café event and dialogical community development. Common themes include setting the environment, developing a common aim and relationship building. Research limitations/implications: A limitation of this paper is that only three case studies are provided, further examples would provide a greater pool of exemplars for others to draw on. However, by focusing upon student nurse education in learning environment, these examples are transferable to other settings. Practical implications: The practical applications are summarised in a four-step model that can help develop co-productive teaching methods; enable educators to set the climate and generate an understanding of co-production that empowers students and service users. Social implications: The emphasis and relevance of promoting co-productive working habits early on in nurses' mental health nursing careers will enable them to raise awareness of future social implications for a range of client groups. Originality/value: This paper focuses upon mental health student nurses whilst providing an innovative model to facilitate co-production experiences applicable in a range of settings.